Adverse Outcomes among Low-Risk Pregnancies at 39 to 41 Weeks: Stratified by Birth Weight Percentile - Mendez-Figueroa, Hector; Chen, Han Yang; Chauhan, Suneet P. (American Journal of Perinatology, 2020)
Objective This study aimed to assess the risk of adverse outcomes among low-risk pregnancies at 39 to 41 weeks, stratified by birth weight percentile.Study Design This retrospective cohort study utilized the U.S. vital statistics datasets (2013–2017) and evaluated low-risk women with nonanomalous cephalic singleton gestations who labored and delivered at 39 to 41 weeks, regardless of ultimate mode of delivery. Newborns were categorized as small (<10th percentile), large (>90th percentile), or appropriate (10–90th percentile) for gestational ages (SGA, LGA, and AGA, respectively). The primary outcome, composite neonatal adverse outcome (CNAO), included Apgar's score <5 at 5 minutes, assisted ventilation >6 hours, seizure, or neonatal death. The secondary outcome, composite maternal adverse outcome (CMAO), included intensive care unit admission, blood transfusion, uterine rupture, or unplanned hysterectomy. Multivariable Poisson's regression was used to estimate the association (using adjusted relative risk [aRR] and 95% confidence interval [CI]).Results Of 19.8 million live births during the study interval, approximately 8.9 million (44.9%) met the inclusion criteria, with 9.9% being SGA, 9.2% being LGA, and 80.9% being AGA. SGA newborns delivered at 40 (aRR = 1.17; 95% CI: 1.12–1.23) and at 41 weeks (aRR = 1.55; 95% CI: 1.45–1.66) had a higher risk of CNAO than at 39 weeks. Similarly, LGA newborns delivered at 40 (aRR = 1.13; 95% CI: 1.07–1.19) and 41 weeks (aRR = 1.44; 95% CI: 1.35–1.54) and AGA newborns delivered at 40 (aRR = 1.24; 95% CI: 1.21–1.26) and 41 weeks (aRR = 1.57; 95% CI: 1.53–1.61) also had a higher risk of CNAO than at 39 weeks. CMAO was also significantly higher at 40 and 41 weeks than at 39 weeks, regardless of whether the mothers delivered SGA, LGA, or AGA newborns.Conclusion Among low-risk pregnancies, the risks of composite neonatal and maternal adverse outcomes increase from 39 through 41 weeks' gestation, irrespective of whether newborns are SGA, LGA, or AGA.
Keywords: neonatal outcomes; low-risk pregnancy; term; birth weight